Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1378/chest.10-1253
|View full text |Cite
|
Sign up to set email alerts
|

COPD in Never Smokers

Abstract: Background:Never smokers comprise a substantial proportion of patients with COPD. Their characteristics and possible risk factors in this population are not yet well defined.Methods:We analyzed data from 14 countries that participated in the international, population-based Burden of Obstructive Lung Disease (BOLD) study. Participants were aged ≥ 40 years and completed postbronchodilator spirometry testing plus questionnaires about respiratory symptoms, health status, and exposure to COPD risk factors. A diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
177
5
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 431 publications
(210 citation statements)
references
References 48 publications
20
177
5
8
Order By: Relevance
“…In the combined analysis of data obtained using the BOLD methodology in 14 countries, no association between AFO and a history of previous PTB was found [21]. In a multivariate analysis of 4,291 never-smokers, the OR was 1.47 (95% CI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the combined analysis of data obtained using the BOLD methodology in 14 countries, no association between AFO and a history of previous PTB was found [21]. In a multivariate analysis of 4,291 never-smokers, the OR was 1.47 (95% CI.…”
Section: Resultsmentioning
confidence: 99%
“…Foremost among these risk factors are tobacco (cigarette) smoking, biomass exposure, childhood lung infections and occupational exposures, including exposure to dust, gases and fumes [3]. The absence of a tobacco-smoking history occurs in over 20% of patients fulfilling the criteria for COPD by spirometry and has been reported in population-based studies from many countries, thereby demanding closer examination of the role of other factors in the development of COPD [4,21]. Whether TB should be added to the list of recognized exposures for the future development of COPD, is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, never-smokers constitute a considerable part of those suffering from COPD. Lamprecht et al [3] have indicated that 27.7% of the people who suffered from COPD had never smoked, and in those cases other risk factors for the disease development, including occupational ones, play an important role. Marine et al, in the study of 3400 miners over a 10-year period, assessed an independent contribution of smoking and exposure to respirable dust to clinically significant measures of respiratory dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) is a cause of increasing morbidity and mortality in Poland and worldwide [1][2][3]. According to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines of 2016, it is a common preventable and treatable disease, which is characterized by an airflow limitation that is usually progressive and associated with an enhanced chronic inflammatory response to noxious particles or gases in the airways and in the lungs [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, in 3-11% of cases disease manifestation occurs at a younger age in non-smoking persons [3][4][5]. The causes of chronic bronchopulmonary pathology in the given group of patients are supposed to be such pathological factors as prematurity and a heavy course of lower respiratory tract infection (LRTI) acting in the perinatal period and during the first three years of life, and leading to the impairment of the lung growth and development [6,7].…”
mentioning
confidence: 99%